Systematic Analysis of Survival-Associated Alternative Splicing Signatures in Thyroid Carcinoma - Han, Baoai; Yang, Minlan; Yang, Xiuping; Liu, Mengzhi; Xie, Qiang; Fan, Guorun; Hosseini, Davood K.; Yu, Jintao; Song, Peng; Chen, Xiong; Sun, Haiying (Frontiers in Oncology, 2021)
Alternative splicing (AS) is a key element for the diversity of mRNA and protein, and splicing dysfunction is related to cancer progression. The incidence of thyroid cancer (THCA) has increased sharply over the past decades. Here, we analyzed RNA-seq data and generated an AS maps of THCA patients filtered from public data in TCGA database. Univariate analysis yielded 825 AS events related to survival. Five prognostic models of AA, AD, AT, ES, and ME events were obtained through lasso and multivariate analysis, and the final prediction model is established by integrating all AS events in the five prediction models. Kaplan-Meier survival analysis showed that the overall survival rates of low-risk patients and high-risk patients were significantly different, and overall survival rates of patients in the high-risk group was significantly shorter than that in the low-risk group. ROC results revealed that the prognostic capabilities of each model in 3, 5, and 8 years were all greater than 0.7, and the final prognostic models were all greater than 0.9. Compared with the model based on individual events, the final prediction model can predict the prognosis of patients better. Other databases and qPCR verification were also found that most of the model genes were consistent with our previous results. In addition, Gene set enrichment analysis showed that abnormal AS events may play a key role in tumor development and progression of THCA by participating in changes of cell molecular structure, homeostasis of cell environment and changes of cell energy. Finally, a splicing correlation network was established to reveal the potential regulatory patterns between predicted splicing factors and candidate AS events. In summary, AS may could be ideal indicators in the prognosis of THCA. Our results help to elucidate the underlying mechanism of AS in the process of THCA tumorigenesis and broaden the prognostic and clinical application of molecular targeted therapy for THCA.